Traditional Belief Rituals and Taboos in the Manora Performance of Arunnoi So Eeb-Uwab Sin at the Songkhla Lake (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACTNora or Manora Rong Khru in Songkhla is a heritage performance art deeply rooted in ritual beliefs, as it involves ceremonies inviting the ancestral spirits of Manora lineage to receive homage. This study addresses the gap in understanding of Manora rituals in contemporary society, where Manora performances are now merely viewed as cultural performances, whereas in reality, they represent a profound spiritual heritage belief deeply embedded in Southern Thai tradition. Therefore, this study examines the rituals and traditional beliefs of the Manora Arunnoi So Eeb-Uwab Sin group, with particular emphasis on preserving the authenticity of rituals, rules, and prohibitions that must be observed by their descendants in the current social context. Additionally, these rituals aim to introduce new generations to the art of Manora. The study focuses on the ritual beliefs of Manora Arunnoi So Eeb-Uwab Sin in Songkhla Province, including the strict rules and prohibitions upheld by the descendants of the Manora Arunnoi So Eeb-Uwab Sin group. This qualitative research collected data through observation and interviews with an expert from the Manora Arunnoi So Eeb-Uwab Sin group in Songkhla Province. The findings explain the ritual beliefs of Manora, including matters that constitute rules and prohibitions for the descendants of the Manora Arunnoi So Eeb-Uwab Sin group in Songkhla Province. The study identified 10 ceremonial beliefs: beliefs about Khru Mor Nora, beliefs about redemption, beliefs about celebrating Serd and tying the great cloth, beliefs about Taeng Khe, beliefs about healing diseases, beliefs about Yiebsen, beliefs about hair cutting, beliefs about dancing with bracelet insertion, beliefs about Khaosong and Rangsong, and beliefs about black magic.ABSTRAKNora atau Manora Rong Khru di Songkhla merupakan persembahan seni warisan yang sarat dengan ritual kepercayaan kerana ia adalah upacara menjemput nenek moyang keturunan manora hadir untuk memberi penghormatan kepada roh moyang manora. Kajian ini membincangkan jurang pemahaman terhadap ritual manora dalam masyarakat kontemporari di mana persembahan manora kini dilihat hanya sebagai seni persembahan budaya semata-mata, sedangkan hakikatnya ia merupakan warisan kepercayaan spiritual yang mendalam dalam tradisi masyarakat Thailand Selatan. Justeru, kajian ini meneliti ritual dan kepercayaan tradisional Kumpulan Manora Arunnoi So Eeb-Uwab Sin dengan memberi tumpuan khusus kepada aspek pemeliharaan keaslian ritual, peraturan, dan larangan yang perlu dipatuhi oleh keturunannya dalam konteks sosial semasa. Selain itu, ritual ini juga bertujuan untuk memperkenalkan generasi baharu yang bakal melangkau ke seni manora. Kajian ini berfokus kepada ritual kepercayaan Manora Arunnoi So Eeb-Uwab Sin di Wilayah Songkhla. Di samping itu, terdapat peraturan dan larangan yang dipegang teguh bagi keturunan kumpulan Manora Arunnoi So Eeb-Uwab Sin. Kajian ini berbentuk kajian kualitatif yang mana pengumpulan datanya dijalankan dengan mengunakan kaedah pemerhatian dan temu bual dengan seorang pakar dalam kumpulan Manora Arunnoi So Eeb-Uwab Sin di Wilayah Songkhla. Hasil kajian ini menjelaskan ritual kepercayaan manora termasuk perkara-perkara yang menjadi peraturan dan larangan bagi keturunan kumpulan Manora Arunnoi So Eeb-Uwab Sin di Wilayah Songkhla. Kajian mendapati bahawa terdapat 10 upacara kepercayaannya, iaitu kepercayaan tentang Khru Mor Nora, kepercayaan untuk menebus kesalahan, kepercayaan tentang meraikan Serd dan mengikat kain besar, kepercayaan tentang Taeng Khe, kepercayaan tentang penyembuahan penyakit, kepercayaan tentang Yiebsen, kepercayaan dalam memotong rambut, kepercayaan tentang menari dengan sisipan gelang, kepercayaan tentang Khaosong dan Rangsong dan kepercayaan tentang ilmu hitam.
Keywords: Belief Ritual; Manora Arunnoi So Eeb-Uwab; Songkhla Province; Traditional